A funç\~ao social da propriedade e o direito à cidade: Teoria e prática atual - Colin Crawford (Instituto de Pesquisa Econômica Aplicada (IPEA), 2017)
– This text undertakes to examine two questions. First, the text considers the intellectual roots of two celebrated and discussed concepts - in Brazil and in the world, specifically the social function of property - enshrined in the 1988 Constitution - and the right to the city, which is guaranteed by Law 10.257 of 2001 (the City Statute). This contribution suggests that the union of these two ideas in Brazil is curious from an intellectual point of view. This is because the social function of property originated, in part, as an intellectual reaction to the extremism of the socialist (and in turn, communist) ideas of the era, while the right to the city has been formulated by a Marxist intellectual. Nevertheless, in the Brazilian articulation of these ideas, the two ideas are considered complementary, and with success. Second, and in a demonstration of the successful intellectual marriage of the two ideas, the text examines more than thirty cases from Brazilian courts alleging violations of the right to the city and the social function of property. While there exists a common perception that Brazilian courts are conservative with respect to urban matters, the evidence of this research shows a high level of awareness about these concepts on the part of the courts, which defend the rights of population to them - concluding that property needs both to respect its social function and that all citizens have a right to the city. The text concludes with the suggestion, therefore, that, in the future, the mobilization in favor of these concepts needs to come from other social sectors, using the favorable court decisions to realize the aspiration of the two concepts.
Keywords: Y80; 330; urbanism; social function of property; right to the city; urban jurisprudence; puplic participation